Schematic rock art paintings in Portugal: an approach to the female universe at Lapa dos Gaviões - Martins, Andrea (2022)
Schematic Rock Painting is a well-defined rock art cycle in today's Portuguese territory, with shelters from north to south, with a very diverse iconography, execution techniques and implantation patterns. These manifestations of agro-pastoral societies often include scenes or mythographies, related to everyday aspects, real or symbolic. In Lapa dos Gaivões we find several panels, distributed over all surfaces, with scenes with anthropomorphs having great relevance. However, the schematic characteristics of these typologies prevent us from recognizing formal and anatomical characters. The female-male dichotomy can be defined from one of the panels, where we find the association of an anthropomorph with a set of bars, with the same morphology being repeated in other scenes. The relationship with the lunar cycle and the female fertility cycle allows us to make considerations about the economic and social organization of these communities, and the iconographic organization does not reveal sexual inequality being female and male in the same level of representation.